2006
DOI: 10.1007/s10546-006-9095-z
|View full text |Cite
|
Sign up to set email alerts
|

Micrometeorological Measurements in a Street Canyon during the Joint ATREUS-PICADA Experiment

Abstract: In order to investigate the microclimatic conditions in a street canyon, a physical model was used to conduct the Joint ATREUS-PICADA Experiment (JAPEX) in situ experimental campaign. Four lines of buildings simulated by steel containers were installed to form three parallel street canyons at 1:5 scale, with width/height aspect ratio approximately 0.40. The reference wind and atmospheric conditions were measured, as well as the flow velocity and direction in the street. Preliminary results concern street canyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
(20 reference statements)
3
26
0
2
Order By: Relevance
“…Due to a lack of flow measurements, the detailed dynamics within these thin layers are not understood but the effect of the temperature differences on the larger-scale flow dynamics within the street canyon was nonetheless found to be negligible. Similar conclusions were drawn by Idczak et al (2007) from their joint ATREUS-PICADA experiment (ATREUS: Advanced Tools for Rational Energy Use towards Sustainability; PICADA: Photo-catalytic Innovative Coverings Applications for Depollution, Demilecamps and André 2005). The wind tunnel study by Kovar-Panskus et al (2002) on a square section cavity likewise demonstrated a very weak secondary flow near the ground at very low Froude number (based on the freestream velocity, canyon height and the difference between freestream reference temperature and the heated wall temperature) but found no evidence of large wall heating effects on the canyon flow field.…”
Section: Introductionsupporting
confidence: 62%
“…Due to a lack of flow measurements, the detailed dynamics within these thin layers are not understood but the effect of the temperature differences on the larger-scale flow dynamics within the street canyon was nonetheless found to be negligible. Similar conclusions were drawn by Idczak et al (2007) from their joint ATREUS-PICADA experiment (ATREUS: Advanced Tools for Rational Energy Use towards Sustainability; PICADA: Photo-catalytic Innovative Coverings Applications for Depollution, Demilecamps and André 2005). The wind tunnel study by Kovar-Panskus et al (2002) on a square section cavity likewise demonstrated a very weak secondary flow near the ground at very low Froude number (based on the freestream velocity, canyon height and the difference between freestream reference temperature and the heated wall temperature) but found no evidence of large wall heating effects on the canyon flow field.…”
Section: Introductionsupporting
confidence: 62%
“…The boundary-layer thickness δ depends on the surface roughness and on the fetch. The value of δ is not well known for urban canopy surfaces, especially for building walls: our recent velocity measurements close to a flat vertical wall show that the dynamic boundary layer along a facade does not present the typical features of a wind-tunnel boundary layer over a horizontal rough plate (Maro et al 2013) while the temperature measurements of Idczak et al (2007) showed a very thin thermal boundary layer along a vertical facade, about 50 mm in thickness. On the other hand, it is probable that thick boundary layers may develop rapidly along real facades with obstacles such as windows, blinds and balconies, but experimental evidence is lacking.…”
Section: Computation Methodsmentioning
confidence: 78%
“…Rather than a theoretically-based modelling this h c computation must be seen as a pragmatic method empirically based on the results of the urban campaigns BUBBLE (Christen 2005) and JAPEX (Idczak et al 2007). …”
Section: Computation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more attention has been paid to the impact of thermal forcing on street-canyon flow. Field measurements have shown the temporal variation of street-canyon flow with a diurnal solar cycle (Nakamura and Oke 1988;Louka et al 2002;Eliasson et al 2006;Offerle et al 2007;Idczak et al 2007). Laboratory experiments (Uehara et al 2000;Kovar-Panskus et al 2002) and two-dimensional numerical experiments (Sini et al 1996;Baik 1999, 2001;Xie et al 2005;Cheng et al 2009) were performed to examine the effects of solar heating on street-canyon flow.…”
Section: Introductionmentioning
confidence: 99%